EFFECTS OF DRUGS ABUSE ON ACADEMIC ACHIEVEMENT OF BASIC SCIENCE STUDENTS IN COLLEGE OF EDUCATION AKAMKPA, CROSS RIVER STATE. - JULIUS OGRI, ACHIGBE; OJI EKPO, EFFIONG; CHARLES EGBONYI, IGIRI, (IJRDO - Journal of Social Science and Humanities Research, 2017)
This study investigates the effects of drugs abuse on Basic science students’ academic achievement in Cross River State College of Education Akamkpa. Systematic random sampling was used to select 250 students from the main population. Two instruments were used to collect data for the study, that is the students drug abuse Questionnaire (SDAQ) and Basic science achievement test (BSAT). A pilot test was conducted with a reliability index of the Questionnaire and the achievement test as 0.75 and 0.81 using the Cronbach-Alpha and Kuder-Richardson (K-20) methods respectively. Three (3) hypotheses were formulated and analyzed using independent t-test. The findings showed that drugs have a significant effect on students’ academic achievement and the peer groups have a greater influence on the intake of drugs among the students. It was recommended that there should be establishment of counseling centers for all levels of education in Nigeria.